Microleakage in class V cavities prepared using conventional method versus Er:YAG laser restored with glass ionomer cement or resin composite - DURMUŞ, BAŞAK; KARGÜL, BETÜL; EREN GİRAY, FİGEN; BEKİROĞLU, GÜLNAZ NURAL; PEKER, MEHMET SERTAÇ (TAYLOR & FRANCIS LTD, 2017)
This study evaluated the effect of tooth preparation method (diamond bur vs. Er:YAG laser) on the microleakage levels of glass ionomers and resin composite. Human permanent premolars (N = 80) were randomly divided into two groups (n = 40). Cavities on half of the teeth were prepared using diamond bur for enamel and carbide bur for dentin and the other half using Er: YAG laser. The teeth were randomly divided into four groups according to the restoration materials, namely (a) ChemFil Rock (CFR), (b) IonoluxAC (IAC), (c) EQUIA system (EQA) and one resin composite (d) AeliteLS (ALS) (n = 10 per group). Microleakage (mu m) was assessed at the occlusal and gingival margins after dye penetration (0.5% basic fuchsine for 24 h). On the occlusal aspect, while the cavity preparation types significantly affected the microleakage for CFR (p = 0.015), IAC (p = 0.001) glass ionomer restorations, it did not show significant effect for glass ionomer EQA (p = 0.09) and resin composite ALS (p = 0.2). Er: YAG laser presented less microleakage compared to bur preparation in all groups except for EQA. On the gingival aspect, microleakage decreased significantly for CFR (p = 0.02), IAC (p = 0.001), except for EQA where significant increase was observed (p = 0.001) with the use of Er: YAG laser. Microleakage decrease was not significant at the gingival region between diamond bur and Er: YAG laser for ALS (p = 0.663). At the occlusal and gingival sites in all groups within each preparation method, microleakage level was not significant.
Keywords: Dental lasers; Er:YAG laser; glass ionomer; microleakage; resin composite; ER-YAG LASER; IN-VITRO; BOND STRENGTH; RESTORATIONS; CARIES; FORMULATIONS; BUR